The First Population-Based Cancer Survey in Kerman Province of Iran - A Sadjadi; MJ Zahedi; S Darvish moghadam; M Nouraie; M Alimohammadian; A Ghorbani; S Bahmanyar; MA Mohagheghi; R Malekzadeh (Tehran University of Medical Sciences, 2007)
Background: Cancer is the second most common cause of non-accidental death in Iran. Geographical, racial and habitual differences have led to the variation in the incidence of cancer in different regions of this country. This study was performed to determine the incidence of cancer in the Kerman Province, central Iran. Methods: All newly diagnosed cases of cancer in the Kerman Province were recorded in a five-year period (1996-2000). Results: In all, 5884 new cases (55.7% males) of cancer were found after elimination of repeated cases. Based on age-standardized incidence rates (ASR) the most common cancers in men were stomach (10.2), lung (7.1), bladder (6.7), colorectal (5.9) and non-Hodgkin's lymphoma (5.8), while in women the most common cancers were breast (16.9) colorectal (5.9), stomach (5.1), leukaemia (4.6) and non-Hodgkin's lymphoma (2.8). For all cancers, ASR was 76 for males and 68 for females. Conclusion: The results indicate that upper gastrointestinal cancer, especially oesophageal cancer is very rare in central Iran in contrast to northern Iran, although these types of cancers are some of the most common cancers in the Kerman Province.